9514 1404 393
Answer:
- to interest: $532.97
- to principal: $54.23
- new balance: $79,891.90
Step-by-step explanation:
The interest is found by multiplying the monthly rate by the balance on the loan. For the first month, the balance is the loan amount.
$79,946.13 × 0.08 ×(1/12) . . . . . one month = 1/12 year
= $532.97
The interest amount in the first payment is $532.97.
__
The amount of the first payment that goes to principal is what is left after the interest is paid:
$587.20 -532.97 = $54.23 . . . amount to principal
__
The new balance is the previous balance less the amount to principal:
$79,946.13 -54.23 = $79,891.90 . . . new balance
Alright, let's do all of these (though this is a bit long).
1.
The constant is 1.8. All other values are coefficients to variables, which as the name implies will change.
2.
1 hour is 60 minutes, 1 minute is 60 seconds.
So, 4.2 *60 *60 = 15120 seconds.
3.
<span>−5x−4(x−6)=−3-5x-4(x-6)=-3
Let's move all x to one side, and all other numbers to another.
-5x-4(x-6)=-3-5x-4(x-6)=-3
x can be any value you want, if you actually solve this you'll only end up with -3 = -3, which is correct, of course.
Let me show you:
</span><span>−5x−4(x−6)=−3-5x-4(x-6)=-3
+5x +4(x-6) +5x +4(x-6)
-3 = -3
The value of x is irrelevant, then. X can be any real number.
4.
I'm going to assume it was an error in printing with this? If not please correct me.
m=a+2b(or b2)
subtract 2b from each
a=m-2b
(This question seems kind of odd. We should probably address this in the comments.)
5.
</span><span>5(x−2)<−3x+6
Move all x to one side, numbers to other.
5x-10<-3x+6
+3x +3x
+10 +10
8x<16
/8
<span>x < 2
</span>6.
y-3=3(x-5)
alright, to find zeros set one variable to zero and solve
x first
-3=3x-15
+15 +15
3x=12
/3
x=4
x-int is (4,0)
now y
</span>y-3=3(0-5)
y-3=-15
+3 +3
y=-12
so y-int is (0,-12)
i've got to sleep now so i'll do the rest tomorrow. Sorry for the incomplete answer.
![x^\circ = x^\circ +360n](https://tex.z-dn.net/?f=x%5E%5Ccirc%20%3D%20x%5E%5Ccirc%20%2B360n)
where n is a whole number
Answer:
The answer is: f(x) = -2x^2 - 4x + 30
Step-by-step explanation:
Given:
f(x)=-2(x-3)(x+5)
Solve (x-3)(x+5) first, then multiply by -2:
f(x) = -2[(x - 3)(x + 5)]
f(x) = -2[x^2 -3x + 5x - 15]
f(x) = -2[x^2 + 2x - 15]
f(x) = -2x^2 - 4x + 30
Hope this Helps!! Have an Awesome Day!! (-: